Materials characterization of FRP composite seismic retrofits after long-term service in a subarctic Alaskan environment. (18th July 2022) - Milev, Sandra; Goodwin, David G.; Sattar, Siamak; Tatar, Jovan
Highlights: No evidence of chemical degradation of FRP was observed following service in Alaska. Glass transition temperature of FRP composite samples varied significantly. Insufficient saturation of CFRP was observed on the north wall at McKinley Tower. Abstract: This study assesses physical and chemical properties of fiber reinforced polymer (FRP) composite materials aged in Alaska's subarctic climate. Carbon FRP (CFRP) and glass FRP (GFRP) samples were collected in 2019 from the exterior and interior of Ted Stevens International Airport (TSIA, retrofitted in 2008) and McKinley Tower (MKT, retrofitted in 2004). Differential scanning calorimetry (DSC) was used to measure glass transition temperature ( T g ) and physical aging, FTIR and Raman spectroscopy were used to investigate potential chemical degradation and degree of cure, and scanning electron microscopy (SEM) to evaluate cross-sectional microstructure, respectively. The results indicate that exposure to the subarctic climate had minimal effect on the composites' T g and chemical properties. The variability in fiber content at MKT and thermal properties at TSIA suggest there were likely some inconsistencies in the FRP installation that may affect load-carrying capacity. Furthermore, some microcracks were observed in the FRP retrofits which may have resulted from a combination of poor fiber impregnation and thermal cycling.